An Empirical Study of Non-Financial Measures’ Emphasis for the Compensation Schemes on Different Categories of Strategic Orientation in Malaysia - Krishnan, Anbalagan; Ramasamy, Ravindran; Joshi, Prem Lal (Indian Journal of Finance, 2014)
Performance management has been a contemporary topic for research. Extensive studies have concentrated on this area and claimed that non financial measures besides financial measures are the essence for today’s business environment. The literature review also asserted that the business performance measurement is highly concentrated on the non-financial indicators and is worthless if not linked to a reward system. Moreover, the measures linked to a reward system, but not as per the strategic direction of the firms, will also flunk the performance measurement system. Thus, this empirical research explored the emphasis of performance measures in relation to the reward system among different categories of Malaysian firms’ strategic orientation. The study was conducted during 2011, and the findings revealed that the emphasis differed among the three categories of Miles and Snow strategic orientations. The firms which adopted a prospector strategy orientation placed a greater emphasis on non-financial performance measures tied to the compensation schemes, and differed from the other two Miles and Snow strategy orientations - analyzers and defenders. On the whole, the findings concluded that when Malaysian firms adopted different categories of strategic orientations, it did have an impact on measures in relation to the compensation schemes.